2015
DOI: 10.1038/srep11484
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic chronoamperometry for probing kinetics of anaerobic microbial metabolism – case study of Faecalibacterium prausnitzii

Abstract: Monitoring in vitro the metabolic activity of microorganisms aids bioprocesses and enables better understanding of microbial metabolism. Redox mediators can be used for this purpose via different electrochemical techniques that are either complex or only provide non-continuous data. Hydrodynamic chronoamperometry using a rotating disc electrode (RDE) can alleviate these issues but was seldom used and is poorly characterized. The kinetics of Faecalibacterium prausnitzii A2-165, a beneficial gut microbe, were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…S5B). This further confirmed that strain 4t3-1-2LB did not excrete dissolved redox mediators to the liquid phase at a detectable concentration in our experiments (47).…”
Section: Resultssupporting
confidence: 89%
“…S5B). This further confirmed that strain 4t3-1-2LB did not excrete dissolved redox mediators to the liquid phase at a detectable concentration in our experiments (47).…”
Section: Resultssupporting
confidence: 89%
“…The presence of char did not modify the sigmoidal shape of the CV nor the difference between the anodic and cathodic plateaus currents. This proves that the total amount of dissolved [ferricyanide + ferrocyanide] stayed constant over the experiment 29 . In particular, it demonstrates the absence of notable adsorption of these redox species on the char surface.…”
Section: Resultssupporting
confidence: 59%
“…Regarding the limited amount of data related to EEC values of biochars as well as some apparent discrepancies, we aimed here to quantify the amount of electrons that can be accepted or donated by wood-based chars pyrolyzed at different HTTs. To do so, we took advantages of highly accurate hydrodynamic electrochemical techniques with rotating disc electrodes (RDE) in order to monitor the redox state of oxidative or reductive solutions reacting with the biochars 29 . After validation of the method, we compared our values with previously published data obtained with similar biochars (feedstock from identical genus – Pinus – and identical HTTs).…”
mentioning
confidence: 99%
“…Further research is required to determine if the use of electrodes for sulfide removal (Figure 4 The current into the circuit should therefore be proportional to the rate at which the electrons are transferred to the electrode by the oxidation reaction (for the anodic process), or diverted by the reduction reaction (for the cathodic process). Hypothesizing that only one metabolic process is occurring on the electrode surface, the produced current can thus be used as a real time parameter to quantify the rate of a specific metabolic process (Prévoteau et al, 2015) or a measure of the substrate concentration available for microbial degradation. Previous studies demonstrated that the current production can be correlated to COD and BOD and that a relationship can be described by Monod type kinetics (Kim et al, 2003;Kumlanghan et al, 2007;Min and Logan, 2004).…”
Section: )mentioning
confidence: 99%